Interest and implementation of construction certification law in Indonesia. Issue 1 (December 2020) - Ekasartika, Trisna; Lim, Jason; Santoso, Iwan B.
Abstract: This research aims to improve the development of Indonesia's construction workforce by analyzing workers knowledge regarding certification law and their implementation in real work, as well as the interests towards certification. The sampling technique used a purposive sampling strategy with research subjects of 100 Indonesian construction workers. Primary data was collected with questionnaire which was further analyzed with Mann-Whitney U test method. From the research, it is obtained that the total percentage of workers knowledge regarding certification law is only 47%. Only 35% of respondents know there is sanction if they are not certified, and 33% are aware of sanctions if they employ uncertified construction workers. Only 34.44% of uncertified workers know of the certification law, while for the certified workers, 62.66% of them know of the law. The implementatian of certification law in real work is 52.68%. Although the number of certified workers are not many, there are high interest of the workers to have certificate which is 70.36%, and in extending certificate which is 77.27%. There is a significant difference between the average interest of uncertified workers and certified workers toward certification. People who have already got certificates are more interested in extending certificate ownership.